Nevus anemicus and neurofibromatosis 1. - Bonifazi, E. (European Journal of Pediatric Dermatology, 2014)
Case 1. A 12-month-old child was first observed due to more than 10 café-au-lait spots greater than 0.5 cm randomly distributed over the whole skin. In the left breast there was a white patch of about 4 cm in diameter, with jagged edges and peripheral satellite lesions, which disappeared under the pressure of the fingers and did not redden under rubbing (Fig. 1). Genetic analysis identified a mutation in the NF1 gene leading to diagnose nevus anemicus in a patient with NF1. Case 2. A 5-year-old girl had about 10 café-au-lait spots of 0.5-2 cm and 2 white patches of about 3 cm on the neck (Fig. 2) that disappeared under pressure of the fingers and did not redden when rubbed. There were no other criteria for the diagnosis of NF1. The physical examination of his father, who did not know he was affected by NF1, showed 7 café-au-lait spots with diameter greater than 2 cm and 5 neurofibromas, of which the largest of 8 x 3 cm above the right knee. The final diagnosis was nevus anemicus in patient with NF1.